Primary Mental Health Care in a New Era - Tselebis, Athanassios; Pachi, Argyro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint entails descriptions of novel issues and challenges for primary mental healthcare regarding both general and vulnerable populations on a global scale. It is intended for health professionals and all who are interested in mental health care at the primary level.